Interval Number Comprehensive Evaluation Model for Assessing the Economic Strength of Guangxi City, China - Kangliang, Wei (วารสารวิทยาลัยนครราชสีมา สาขามนุษยศาสตร์และสังคมศาสตร์, 2025)
This study employs an Interval Number Comprehensive Evaluation Model to assess the comprehensive economic strength of fourteen cities in Guangxi, China, including Nanning, Liuzhou, Guilin, Wuzhou, Beihai, Fang Chenggang, Qinzhou, Guigang, Yulin, Baise, Hezhou, Hechi, Laibin, and Chongzuo. Evaluation criteria encompass the overall economic scale, industrial structure, infrastructure, living standards, and education/health levels. The research adheres to principles of scientificity, conciseness, feasibility, and applicability in constructing an evaluation indicator system. The results were indicated that Nanning, Liuzhou, and Guilin as the top three cities in terms of comprehensive economic strength during the ’13th Five-Year Plan,’ with corresponding interval values [0.0502, 0.0688], [0.1999, 0.2653], and [0.2236, 0.3225]. Cities with medium strength include Beihai, Yulin, Fangchenggang, Qinzhou, Guigang, and Wuzhou, exhibiting interval values between [0.2887, 0.5506]. Cities with weaker economic strength—Chongzuo, Laibin, Baise, Hezhou, and Hechi—show interval values between [0.4362, 0.7128], indicating lower development levels. The research contributes insights into the economic dynamics of Guangxi City, providing a nuanced understanding of its regional development.